IBM z/OS V2R2 : Sysplex - Winnard, Keith (IBM redbooks., 2015)
This IBM® Redbooks® publication helps you to become familiar with the technical changes that were introduced into the Sysplex areas with IBM z/OS® V2R2. This book is one of a series of IBM Redbooks publications that takes a modular approach to providing information about the updates that are contained within z/OS V2R2. This approach includes the following goals: - Provide modular content - Group the technical changes into topics - Provide a more streamlined way of finding relevant information that is based on the topic We hope you find this approach useful and value your feedback.